PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 014 BASILAM BARU - Alpusari, Mahmud Alpusari Mahmud; ', Hotmauli; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract., Background problem in this study is the result of fourth grade students learn science SDN  014 Basilam Baru Kecamatan Sungai Sembilang Dumai is still low or inadequate standards KKM Only 5 people who completed the traditional fashion. For the research study conducted by Application Type STAD Cooperative Learning Model. With the formulation of the problem "Is Application Type STAD Cooperative Learning Model can improve science learning outcomes fourth grade students SDN 014 Basilam Baru?" This study aims to improve science learning outcomes fourth grade students through the implementation of SDN 014 Basilam Baru  STAD cooperative learning. The hypothesis of this study is: if applied STAD cooperative learning model to improve learning outcomes IPA fourth grade students SDN 014 Basilam Baru. This research is a form of Classroom Action Research (CAR). The subjects were fourth grade students of Elementary School 014 New Basilam semester academic year 2013-2014 the number of students 21 students consisting of 15 male students and 6 female students. The data collected in the form of observations and tests student learning outcomes. From the analysis of data collected percentage increase in the activity of the first cycle of the first meeting of teachers 68.75% (Both Categories) kepertemuan II increased to 81.25% (Both Categories) increased in the second cycle the first meeting be 84.37% (Category Very Good) and increased again in second meeting be 93.75% (Very Good category). While the percentage of student activity in the first cycle the first meeting of 59.38% (Category Less) increased at the second meeting to be 75% (Both Categories) and increased again at the first meeting of the second cycle to be 78.12% (Both Categories) and increased again at the meeting of the Second be 87.5% (Both categories). Improved student learning outcomes from the first cycle to the base score is an average of 65.2 into 70.61 with an increase of 10.41 and increase learning outcomes from the first cycle to the second cycle average of 70.61 into 76.33 with an increase 5.72. Students who complete the first cycle is 11 students, while in the second cycle to students who complete 19 students. From the above discussion it can be concluded that through the implementation of STAD cooperative learning model to improve learning outcomes IPA fourth grade studentsSDN 014 Basilam Baru. Keyword : Student team achievement division (STAD), SAINS